2016
DOI: 10.3390/molecules21121630
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Four Tanshinones by UPLC-TQ/MS and Their Pharmacokinetic Application after Administration of Single Ethanol Extract of Danshen Combined with Water Extract in Normal and Adenine-Induced Chronic Renal Failure Rats

Abstract: Salvia miltiorrhiza, one of the major traditional Chinese medicines, is commonly used and the main active ingredients-tanshinones-possess the ability to improve renal function. In this paper, the UPLC-TQ/MS method of simultaneously determining four tanshinones-tanshinone IIA, dihydrotanshinone I, tanshinone I, and cryptotanshinone-was established and applied to assess the pharmacokinetics in normal and chronic renal failure (CRF) rat plasma. The pharmacokinetics of tanshinones in rats were studied after separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…As shown in Tables , the C max of cryptotanshinone and Tan IIA in rats after a single oral dose of Salvia miltiorrhiza extract was significantly higher than that in rats receiving the pure tanshinones (p < 0.05), which was in accordance with previous reports (Cai et al, ; Song, ). Furthermore, the AUC 0‐∞ of cryptotanshinone, Tan IIA, diTan I, and Tan I after a single dose of the Salvia miltiorrhiza extract were found to be 4158.4 ± 1307.0, 791.8 ± 339.4, 562.4 ± 233.7, 301.3 ± 177.3 μg/L·h, respectively, which were increased by about 5.3, 4.9, 1.1 and 2.3 folds compared with that in rats receiving the pure tanshinones (p < 0.05).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Tables , the C max of cryptotanshinone and Tan IIA in rats after a single oral dose of Salvia miltiorrhiza extract was significantly higher than that in rats receiving the pure tanshinones (p < 0.05), which was in accordance with previous reports (Cai et al, ; Song, ). Furthermore, the AUC 0‐∞ of cryptotanshinone, Tan IIA, diTan I, and Tan I after a single dose of the Salvia miltiorrhiza extract were found to be 4158.4 ± 1307.0, 791.8 ± 339.4, 562.4 ± 233.7, 301.3 ± 177.3 μg/L·h, respectively, which were increased by about 5.3, 4.9, 1.1 and 2.3 folds compared with that in rats receiving the pure tanshinones (p < 0.05).…”
Section: Resultssupporting
confidence: 92%
“…(origin of Hebei, China), had a content of cryptotanshinone and tanshinone IIA of 24.5% and 34.3%, respectively. However, another study (Cai et al, ) showed that the content of the constituents in Salvia miltiorrhiza ethanol extract, tanshinone IIA, cryptotanshinone, dihydrotanshinone I, tanshinone I, were 12.63 mg/g, 43.73 mg/g, 10.27 mg/g, and 6.25 mg/g, respectively, which was close to our result. It is speculated that the difference in the content of tanshinones may be due to the difference in the extraction method or the source of Salvia miltiorrhiza (Liu, Li, & Wang, ).…”
Section: Resultssupporting
confidence: 90%
“…Salvia miltiorrhiza (SM), a kind of perennial herb that derived from Salvia genus of the Labiatae family, the dry roots and rhizomes are officially listed in the Chinese Pharmacopoeia [ 1 , 2 ], and it is highly valued and one of the most widely used traditional Chinese medicines (TCM) by virtue of its function to “promote blood circulation and remove blood stasis” that was firstly recorded in Shennong's Classic of Materia Medica (200–300 AD, Han Dynasty). The remarkable effects of S. miltiorrhiza on treatment of complicated cardiovascular diseases and cerebrovascular diseases have been reported during the past decades [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active ingredients in S. miltiorrhiza mainly include hydrosoluble salvianolic acids and liposoluble tanshinones. However, phenolic acids showed poor gut permeability and extremely low bioavailability in plasma after oral administration (Cai et al, ; Li et al, ). Most importantly, since phenolic acids were also extracted in the TDS, it was not appropriate to analyze the in vivo phenolic acids after oral Salvivae Miltionrrhizae UGP and TDS.…”
Section: Resultsmentioning
confidence: 99%